Pengaruh Struktur Modal, Beban Pajak Tangguhan dan Pertumbuhan Penjualan terhadap Penghindaran Pajak - Darma, Sapta Setia; Amelia, Kurnia Zisky (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Tax avoidance is a common financial practice used by companies to reduce tax obligations through legal strategies, but it often raises concerns regarding transparency and ethical corporate behavior. This issue is particularly relevant in the consumer non-cyclical sector, where companies tend to have consistent revenue streams, providing opportunities to engage in structured tax planning. Understanding how financial factors such as capital structure, deferred tax expense, and sales growth influence tax avoidance is important for assessing corporate governance and regulatory compliance. This study aims to analyze the influence of capital structure, deferred tax expense, and sales growth on tax avoidance among companies in the primary consumer goods sector (Consumer Non-Cyclical) listed on the Indonesia Stock Exchange (IDX) during the period 2018–2023. A quantitative research approach was used, employing secondary data obtained from published financial reports. Data analysis techniques include descriptive statistics, panel data regression, classical assumption testing, and hypothesis testing, using Microsoft Excel and E-Views 12. The population consists of 132 companies, with 37 selected through purposive sampling. The findings show that capital structure and deferred tax expense simultaneously have a significant effect on tax avoidance. Partially, capital structure has a positive and significant effect, indicating that companies with higher leverage tend to engage in more tax avoidance practices. Conversely, deferred tax expense and sales growth do not have a significant individual effect, suggesting that these variables may not directly influence a company's tax planning behavior in this sector.